A corpus-based study of semantic treatment of phrasal verbs in Malaysian ESL secondary school textbooks - Zarifi, Abdolvahed; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2015)
Despite their being the most notoriously confusing aspects of English language instruction, phrasal verbs are of high relevance for ESL/EFL learners because knowledge of them is often equated with language proficiency and fluency. With textbooks containing a noticeable number of phrasal verbs, it is of pedagogical significance to see if these combinations are appropriately dealt with in semantic terms. The present corpus-based study was, thus, intended to explore the semantic treatment of these combinations in a pedagogical corpus of Malaysian ESL textbooks. Using WordSmith software and the Oxford Dictionary of Phrasal Verbs as research instruments, the study revealed that despite the overwhelming number of phrasal verbs in the corpus, most of these combinations were presented with a very thin skeleton, as they were repeated in different forms with the same meaning. In addition, some items were presented with their rare and infrequent word meanings. Therefore, the selection and presentation of the word senses of different phrasal verb combinations proved to be more intuitively than empirically motivated.